2022
DOI: 10.21037/atm-22-4477
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes associated with cancer stem cell characteristics in Wilms’ tumor based on bioinformatics analysis

Abstract: Background: Nephroblastoma, also known as Wilms' tumor (WT), remains one of the major causes of tumor-related deaths worldwide in children. Cancer stem cells (CSCs) are considered to be the main culprits in cancer resistance and disease recurrence, which are reported in multiple types of tumors. However, the research on CSCs in WT is limited. Therefore, our study aimed to identify the key genes related to CSCs in WT to provide new ideas for treating WT. Methods:The RNA-seq and clinical data of WT samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Modules enriched for altered-11p15 nonBWS-WT trait mainly showed enrichment of cell cycle and metabolic processes. Many other studies on WT using the WGCNA approach have showed enrichment of cell cycle related processes, indicating it as a major molecular signature for WT [ 77 79 ]. Along with metabolic pathway enrichment, Wang et al have also shown enrichment of PI3K-Akt, FoxO, p53, and TNF signaling pathways, along with many other cancer related pathways in WT, using the WGCNA approach [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modules enriched for altered-11p15 nonBWS-WT trait mainly showed enrichment of cell cycle and metabolic processes. Many other studies on WT using the WGCNA approach have showed enrichment of cell cycle related processes, indicating it as a major molecular signature for WT [ 77 79 ]. Along with metabolic pathway enrichment, Wang et al have also shown enrichment of PI3K-Akt, FoxO, p53, and TNF signaling pathways, along with many other cancer related pathways in WT, using the WGCNA approach [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The uniformly normalized pan-cancer dataset was downloaded from the UCSC database ( https://xenabrowser.net/ ) (Access date: September 15, 2022). The GSE66405 dataset in the GEO database can be employed to verify whether there are differences in the expression of SNHG15 [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Identification of differentially expressed genes. In this study, we searched the GEO database and selected two gene expression profiles (GSE66405 and GSE11024) [29][30][31] . These GSE datasets were downloaded from the NCBI database and all GSE datasets consisted of two groups: WT and normal tissue.…”
Section: Methodsmentioning
confidence: 99%